2017
DOI: 10.1016/j.juro.2017.02.071
|View full text |Cite
|
Sign up to set email alerts
|

Combined Whole Body and Multiparametric Prostate Magnetic Resonance Imaging as a 1-Step Approach to the Simultaneous Assessment of Local Recurrence and Metastatic Disease after Radical Prostatectomy

Abstract: Purpose To report our initial experience using “whole body and dedicated prostate (WB+P)” MRI as a single exam for the assessment of local recurrence and metastatic disease in patients with suspected recurrent prostate cancer (PCa) after radical prostatectomy (RP). Materials and Methods IRB-approved retrospective single-center study. 76 consecutive patients with clinically suspected recurrent PCa following RP underwent combined WB+P-MRI in a single session (10/2014-01/2016). WB+P-MRI scans were evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 24 publications
1
17
0
1
Order By: Relevance
“…Dedicated fusion software enabled multimodality image fusion when needed. Previous studies have shown that when the serum PSA level is 1 ng/mL or less, mpMR detects local recurrence in the prostatic bed in 11%-21% of patients (6,7). Our results were similar, with a detection rate of 15.1% for the entire cohort.…”
Section: Discussionsupporting
confidence: 85%
“…Dedicated fusion software enabled multimodality image fusion when needed. Previous studies have shown that when the serum PSA level is 1 ng/mL or less, mpMR detects local recurrence in the prostatic bed in 11%-21% of patients (6,7). Our results were similar, with a detection rate of 15.1% for the entire cohort.…”
Section: Discussionsupporting
confidence: 85%
“…The role of imaging in these cases is critical. Imaging firstly should be to rule--out poly--metastatic disease not amenable to cure by local treatment alone, and to detect OMD that could benefit from regional salvage therapies 75,76,77 . The detection of OMD at BCR is important since at least one trial has demonstrated that MDT could delay initiation of ADT 8 .…”
Section: Optimal Methods For Imaging Metastases In Patients With Biocmentioning
confidence: 99%
“…WB--MRI can detect metastases at BCR even at (very) low PSA values (median 0.36 ng/ml) 76 (Figure A2). A WB--MRI based study evaluating the distribution of bone and node recurrence showed that metastatic disease was often distant, located beyond usual surgical and radiotherapeutic boundaries for treating BCR 12 .…”
Section: Optimal Methods For Imaging Metastases In Patients With Biocmentioning
confidence: 99%
“…In a study of 76 consecutive patients with suspected PCa recurrence after RP, WB and dedicated prostate MRI was completed successfully in all patients. Suspected disease recurrence was identified in 21% (16/76) of patients, including local recurrence in the prostate bed in 8% (46).…”
Section: Is There Residual Tumor In the Prostate Bed?mentioning
confidence: 99%